Economics of farmers' demand for private irrigation in Nigeria - Takeshima, Hiroyuki; Salau, Sheu; Adeoti, Adetola I.; Okoli, Silas (International Food Policy Research Institute, 2010)
Small-scale private irrigation (SPRI) schemes make up much of the irrigated areas in Nigeria. These irrigated areas, though, are only about three percent of the cultivated area in the country. Constraints on SPRI expansion are investigated by many studies in Nigeria, but key knowledge gaps in at least four areas still need to be resolved. These gaps are: (1) lack of knowledge of water sources; (2) perceptions of risks associated with rainfall and access to good quality water; (3) transaction costs associated with investments in irrigation; and (4) effectiveness of public institutions activities in SPRI.